Evolution of Rajabasa Volcano in Kalianda Area and Its Vicinity, South Lampung Regency - Bronto, Sutikno; Asmoro, P.; Hartono, G.; Sulistiyono, Sulistiyono (Geological Agency, 2012)
DOI:Â 10.17014/ijog.v7i1.132Rajabasa Volcano (Â± 1281 m) and Lampung Tuff, located in the South Lampung Regency, is the main point in order to understand the evolution of Quaternary volcanism in the area. A remote sensing analysis and field geologic work are the methods of the study. The volcanism began with the construction period of the Pre-Rajabasa composite cone which was followed by the destruction period of the cone to form the Pre-Rajabasa Caldera having ca. 25 km in diameter. The present Rajabasa Volcano, along with cones of flank eruptions and monogenesis, has appeared in the Pre-Rajabasa Caldera depression. Those volcanic activities are considered as the second construction period. During the first and the second construction periods, basaltic to andesitic lava flows, pyroclastic breccias, and tuffs were erupted. The Rajabasa eruption points moved in WNW - ESE direction, which were possibly controlled by a subsurface weak zone. The Pre-Rajabasa Caldera erupted voluminous Lampung Tuffs having rhyolite in composition, and they are considered as a combination of pyroclastic falls, flows, and surges, or pyroclastic density currents.